Evolving the capacity to understand the actions, intentions, and goals.[article]. - Hauser, Marc; Wood, Justin
We synthesize the contrasting predictions of motor simulation teleological theories of action comprehension and present evidence from a series of studies showing that monkeys ans apes-like humans-extract the meaning of an event by (a) going beyond the surface appearance of actions, attributing goals and intentions to the agent; (b) using details about the environment to infer when an action is rational or irrational;(c)making predictions about an agent's goal and the most probable action to obtain the goal, within the constraints of the situation;(d)predicting the most probable outcome of actions even when they are physiologically incapable of producing the actions; and (e)combining information about means and outcomes to make decisions about social interactions, some with moral relevance. These studies reveal the limitations of motor simulation theories, especially those that rely on the notion of direct matching and mirror neuron activation. They provide support, however, for a teleological theory, rooted in an inferential process that extracts information about actions means, potential goals, and the environmental constraints that limit rational action.
Keywords: Motor representations; Mirrors neurons; Mental states; Evolution; Morality; Comparative psychology